Direito à imagem: conceito jurídico pleno da própria imagem - Ribeiro, Iara Pereira (2013)
The thesis aims to show that the image of person for Juridical Science understands the original and the reproduction and that this image is a whole composed of matter and form, which encompasses the physic, body, voice, gestures, moods, etc. Considering the full image concept is examined various theories about the right of the image to define it as an autonomous right and its characteristics the legal concept fully developed in this thesis, examined the various theories on the image to the law to define it as an autonomous right and their characteristics, analyze its elements: the subject of law (image of unborn and legal entity image), the object (scientific image and picture of things) and the content that is the right to dispose, the limits of the right to use his image and extinction. And finally, it was the subject of tort law from the perspective of the image, to show that the so called institutional and aesthetic damage are simply: damage to the image. And this damage is distinct from the material and moral, allowing overlapping